E2F1-driven EXOSC10 transcription promotes hepatocellular carcinoma growth and stemness: a potential therapeutic target - Haoyue Deng; Dingyong Wu; Yongpeng He; Xiaolei Yu; Jifei Liu; Yanrui Zhang; Bing Leng; Xiaofeng Yuan; Liguo Xiao (Hereditas)
Abstract Background E2F Transcription Factor 1 (E2F1) is a transcription factor that plays a crucial role in the growth of many cancers, including hepatocellular carcinoma (HCC). Herein, this study probed the functions and underlying mechanisms of E2F1 in HCC tumorigenesis. Methods The expression profiles of E2F1 and Exosome Component 10 (EXOSC10) were detected using qRT-PCR and western blotting. Functional experiments were carried out using 5-ethynyl-2’-deoxyuridine (EdU), flow cytometry, tube formation, and sphere formation assays in vitro, as well as xenograft experiments in vivo, respectively. Stemness-related proteins were assayed using western blotting. The interaction between E2F1 and EXOSC10 was verified using bioinformatics analysis and dual-luciferase reporter assay. Results E2F1 was highly expressed in HCC tissues and cells, and was associated with advanced TNM stage, distant metastasis, and short survival rate. Functionally, knockdown of E2F1 suppressed HCC cell proliferation, angiogenesis, and stemness, and induced cell apoptosis. Mechanistically, E2F1 directly bound to the promoter region of EXOSC10 to up-regulate its expression. EXOSC10 silencing impaired HCC cell proliferation, angiogenesis, and stemness. Moreover, the anticancer effects of E2F1 knockdown were reversed by EXOSC10 elevation. In vivo assay, E2F1 deficiency suppressed HCC tumor growth and eliminated cancer stemness, while these effects were abolished by EXOSC10 up-regulation. Conclusion E2F1 promotes EXOSC10 transcription and then facilitates HCC growth and cancer stemness, revealing a potential target for HCC therapy.